Preservation of liver with Euro-Collins solution: Evaluation of ultrastructural alterations - (:unkn) unknown (My University, 1999)
Objective: The aim of this study was to investigate time-related ultrastructural alterations in the rat liver during Euro-Collins perfusion and storage. Material-Methods: Rat liver pieces were placed in cold (4°C) Euro-Collins solution and stored for 0, 3, 6 and 12 hour periods. Morphologic investigations were performed using electron microscopy. Results: Electronmicrographs from the 3 hour and 6 hour perfusions showed a slight degree of hepatocellular degeneration. Extremely swollen and degenerated hepatocytes were observed at the 12(th) hour of preservation period. Conclusion: It is concluded that the safe storage period for the rat liver in Euro-Collins solution is less than 12 hours.
Keywords: Euro-Collins solution; Liver; Tissue preservation; Ultrastructure